2021
DOI: 10.1021/acs.est.1c01283
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Characterization of Compound Selectivity for Oxidation and Oxidative Alterations of Dissolved Organic Matter by Manganese Oxide

Abstract: Manganese (Mn) oxides can oxidize dissolved organic matter (DOM) and alter its chemical properties and microbial degradability, but the compound selectivity for oxidation and oxidative alterations remain to be determined. We applied ultrahigh mass spectrometry to catalog the macromolecular composition of Suwannee River fulvic acid (SRFA) before and after oxidation by a Mn oxide (δ-MnO 2 ) at pH 4 or 6. Polycyclic aromatic hydrocarbons, polyphenols, and carbohydrates were more reactive in reducing δ-MnO 2 than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 75 publications
1
44
2
Order By: Relevance
“…Furthermore, the formulas that increase in relative intensity after reaction span a greater range of the van Krevelen diagram than the identified oxidation products, which are typically confined to the lignin-like region of the plots and are consistent with selective phenol-like reactions within the pool of DOM molecules (Figures and S11). The scattered product formulas support the observed differences in aromaticity and molecular weight measures using both bulk measurements and FT-ICR MS analysis (Table S6) as well as evidence of non-oxidative transformations occurring in the DOM pool and are supported by observations made after reacting high concentrations (∼300 mg-C L -1 ) of Suwannee River fulvic acid with δ-MnO 2 at pH 4 . Although there are differences in bulk DOM compositional changes and a wide range of products are generated by the reaction of DOM and acid birnessite, these results demonstrate that MnO 2 reacts selectively with electron-rich, lignin-like formulas even in waters containing highly diverse DOM.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Furthermore, the formulas that increase in relative intensity after reaction span a greater range of the van Krevelen diagram than the identified oxidation products, which are typically confined to the lignin-like region of the plots and are consistent with selective phenol-like reactions within the pool of DOM molecules (Figures and S11). The scattered product formulas support the observed differences in aromaticity and molecular weight measures using both bulk measurements and FT-ICR MS analysis (Table S6) as well as evidence of non-oxidative transformations occurring in the DOM pool and are supported by observations made after reacting high concentrations (∼300 mg-C L -1 ) of Suwannee River fulvic acid with δ-MnO 2 at pH 4 . Although there are differences in bulk DOM compositional changes and a wide range of products are generated by the reaction of DOM and acid birnessite, these results demonstrate that MnO 2 reacts selectively with electron-rich, lignin-like formulas even in waters containing highly diverse DOM.…”
Section: Resultssupporting
confidence: 75%
“…Thus, DOM remaining in solution is slightly reduced relative to the initial DOM, contradicting FT-IR observations of reacted DOM, ,, as well as measures of Mn reduction in this data set and previous literature studies. ,,, However, weighted values encompass all transformations to the DOM pool including non-oxidative reactions and fractionation due to selective sorption and colloidal organic matter–Mn­(II/III) formation. Studies using a fulvic acid isolate or DOM derived from biochar have similarly observed that O:C w can either increase or decrease after reaction with Mn oxides. , While decreases in O:C w indicate reduction of C in the bulk DOM pool, this result does not negate other measures of aromaticity and molecular weight which suggest that oxidation occurs. Rather, more specific evidence supporting the formation of oxidized product formulas is necessary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manganese (Mn) minerals are ubiquitous oxidants in the soil systems, and the redox reactions between organic carbon and Mn oxide occur extensively (Fig. 3) (Ma et al 2020;Zhang et al 2021). Manganese could be the dominant redox moiety in soil, especially in the surface layer, even when compared with iron minerals (Jones et al 2020).…”
Section: Redox-induced Transformation Of Ptes By the Redox Cycle Of M...mentioning
confidence: 99%